FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PELAYANAN PASIEN POLI GIGI DI PUSKESMAS BANDA SAKTI KECAMATAN BANDA SAKTI KOTA LHOKSEUMAWE - Bahri, Khairul (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2016)
BPFK Medan serves testing, calibration and radiation protection of medical devices as a duty in securing health facilities. The working area of ​​BPFK Medan consists of all health services located in Aceh, North Sumatera, Riau, West Sumatra, Riau Islands, Jambi and Bengkulu. A vast working area brings a lot of customer service demand. As calibration service provider for medical devices, BPFK Medan needs to satisfy customer satisfaction by providing quality services. Therefore, research is done to improve service quality by using DMAIC Six Sigma method. Results given, globally, the average BPFK Medan service quality is at 2.22 of sigma level and gap analysis results negative values. Priority for service improvements is focused on complying promised time and prioritized dimension of reliability. The action plan for BPFK Medan is suggested to improve services by evaluating and improving Standard Operating Procedures (SOP), conducting evaluation of calibration working method, providing managerial training for offices and upgrading the capability of calibration officers. Keywords: Customer Satisfaction, Service Quality, Gap Analysis, DMAIC, Six Sigma